2019
DOI: 10.1002/hbm.24778
|View full text |Cite
|
Sign up to set email alerts
|

Proactive inhibition deficits with normal perfusion after pediatric mild traumatic brain injury

Abstract: Although much attention has been generated in popular media regarding the deleterious effects of pediatric mild traumatic brain injury (pmTBI), a paucity of empirical evidence exists regarding the natural course of biological recovery. Fifty pmTBI patients (12–18 years old) were consecutively recruited from Emergency Departments and seen approximately 1 week and 4 months post‐injury in this prospective cohort study. Data from 53 sex‐ and age‐matched healthy controls (HC) were also collected. Functional magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 54 publications
(80 reference statements)
2
29
0
Order By: Relevance
“…In the regional analysis of cerebral perfusion, an effect of tDCS was observed, with reductions of CBF occurring in the right IFG in the sham group, and increases of CBF in the right IFG of the active group. Although FDR correction resulted in nonsignificance, this finding is still of some interest, as there is theoretical and empirical basis for altered right prefrontal and right fronto-parietal perfusion after mTBI (32,(73)(74)(75). The right frontoparietal network is implicated in lateralization of cognitive and emotional functions, including inhibition (76), visual attention, and emotional sham.…”
Section: Discussionmentioning
confidence: 99%
“…In the regional analysis of cerebral perfusion, an effect of tDCS was observed, with reductions of CBF occurring in the right IFG in the sham group, and increases of CBF in the right IFG of the active group. Although FDR correction resulted in nonsignificance, this finding is still of some interest, as there is theoretical and empirical basis for altered right prefrontal and right fronto-parietal perfusion after mTBI (32,(73)(74)(75). The right frontoparietal network is implicated in lateralization of cognitive and emotional functions, including inhibition (76), visual attention, and emotional sham.…”
Section: Discussionmentioning
confidence: 99%
“…This concept was further supported in this study which also found that active tDCS was associated with increased CBF in the right inferior frontal gyrus, a brain area likely under the anode, whereas regional CBF of this same area was reduced in sham; although this finding again did not survive statistical correction. Nevertheless, this was interesting because of theoretical and empirical findings that have indicated different right prefrontal and right frontoparietal perfusions after mTBI [ 76 , 79 , 80 , 81 ]. The latter region is likely part of a network that has been associated with inhibition [ 82 ], visual attention, and emotion.…”
Section: Resultsmentioning
confidence: 99%
“…Participants were from an ongoing study examining biomarkers in pmTBI [ 36 ]. Inclusion criteria for mTBI participants were based on the American Congress of Rehabilitation Medicine and the Zurich Concussion in Sport Group guidelines (see details in Supplemental Materials).…”
Section: Methodsmentioning
confidence: 99%